What neuro-otology specialists need for better care of dizzy patients: a national survey - Mantokoudis, Georgios; Zwergal, Andreas; Heg, Dik; Kerkeni, Hassen; Diener, Suzie; Kalla, Roger; Korda, Athanasia; Candreia, Claudia; Welge-Lüssen, Antje; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2024)
Background A substantial fraction of dizzy patients are assessed by neurologists and ear–nose–throat (ENT) physicians. With the differential diagnosis being broad and often different specialties involved, we aimed to assess the interaction with generalists from the specialists’ perspective to identify limitations and needs and to define strategies for improvement in patient care and education by the specialist. Methods One hundred eleven board-certified neurologists (n = 62) and ENT physicians (n = 49) working in Switzerland participated in an online survey. Here, we focused on limitations faced in the diagnostic workup and treatment of the dizzy patient and potential strategies to improve the standard of care and the interaction between generalists and specialists. Descriptive statistical analyses were performed. We hypothesized that those specialists applying modern concepts in history-taking and bedside examination techniques reach a specific diagnosis more often and request fewer referrals. Results Specialists indicated higher confidence in reaching a specific diagnosis for patients presenting with acute dizziness than episodic/chronic dizziness (80% vs. 60%) at the first consultation. Knowledge of the timing-and-trigger concept [odds ratio (OR) = 0.81 (0.67–0.98), p = 0.034], as well as of subtle oculomotor/vestibular signs [OR = 0.80 (0.68–0.94), p = 0.007] was predictive of the self-reported probability of reaching a specific diagnosis in patients with episodic/chronic dizziness, while no such differences were observed in the care of acutely dizzy patients. Further referrals of acutely dizzy patients were significantly higher in neurologists than in ENT physicians (17% vs. 10%, p < 0.001) and in specialists located in the Latin part of Switzerland [OR = 2.84 (1.63–4.93), p < 0.001], while this was not the case for patients with episodic/chronic dizziness. Identified unmet needs included regular communication between physicians (27%/53%; always/often true) and sufficiently detailed information on the previous workup from the referrals (27%/53%). Specialists expressed most interest in hands-on courses/workshops, webinars, and practical guidelines for education. Conclusion In our survey, bedside state-of-the-art assessments were key in reducing the fraction of unclear dizzy cases. Several gaps were identified that should be addressed. Specifically, referring physicians should provide more comprehensive details regarding urgency, prior diagnostics, and treatment. Specifically, when promoting the knowledge of neurologists and ENT physicians, this should be preferentially done by offering a combination of hands-on courses and webinars.